Surface pretreatment effect on the electrochemical reduction of CO2 on polycrystalline copper III aqueous hydrogen carbonate solution - Jumat Salimon,; Maher Kalaji, (Universiti Kebangsaan Malaysia, 2002)
A major obstacle that arises during the electroreduction of carbon dioxide in aqueous solution is the formation of inactive specie on the surface of electrode. The route that leads the formation of carbonate ions during the reduction of CO2 is minimized through surface electro-polarization of the electrode. As the polarization potential is varied from -1.0 to 1.5 V (vs. SCE), an adsorbed carbon monoxide band that shifts from 1889 to 1920 cm-1 appeared, indicating that an adsorbed carbon monoxide is produced from the reduction of CO2, The band was not observed without surface prepolarization or in nitrogen-saturated solution. These results confirm that the "carbonate route" can be overcame and depressed during the electroreduction of CO2 in aqueous solution. Studies performed using other electrodes (Ni and Pt) show the same behaviour although in different potential ranges. Comparison with similar studies reported in recent literature suggests that the history of the electrode and pre-treatment are very critical.